The Earth is all that lasts : Crazy Horse, Sitting Bull, and the last stand of the Great Sioux Nation - Gardner, Mark Lee, 1960- (Mariner Books, 2022)
"A magisterial dual biography of Crazy Horse and Sitting Bull, revealing in groundbreaking new detail the two most legendary and consequential American Indian leaders, who triumphed at the Battle of Little Big Horn and led Sioux resistance in the fierce final chapter of the "Indian Wars." --From book jacket.